2021
DOI: 10.1002/onco.13771
|View full text |Cite
|
Sign up to set email alerts
|

Underrepresentation in Oncology: Identifying and Addressing Structural Barriers

Abstract: Underrepresentation of minority groups in the oncology physician workforce is a pressing issue that may contribute to disparities in cancer research, clinical care, and patient outcomes. To address this, we highlight the role of medical culture and institutions in perpetuating a range of barriers that lead to the persistent underrepresentation of minority medical trainees and physicians. These barriers include an exclusionary medical culture, bias in measures of merit, financial barriers to medical subspecialt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
(13 reference statements)
0
9
0
1
Order By: Relevance
“…Increasing diversity in the primary care and oncology workforce could help reduce provider biases and discrimination in health care settings, 201 improve shared decision making, 202 and increase people of color's satisfaction and trust in health systems 203,204 . A diverse research workforce also broadens scientific inquiry and knowledge and can result in better science 134,205 .…”
Section: Future Directions (Next Steps)mentioning
confidence: 99%
“…Increasing diversity in the primary care and oncology workforce could help reduce provider biases and discrimination in health care settings, 201 improve shared decision making, 202 and increase people of color's satisfaction and trust in health systems 203,204 . A diverse research workforce also broadens scientific inquiry and knowledge and can result in better science 134,205 .…”
Section: Future Directions (Next Steps)mentioning
confidence: 99%
“…11 , 12 Mechanisms underlying these disparities include differences in access to care and follow-up, screening utilization, and health behaviors. 13 , 14 For specific malignancies, studies have also illustrated that the likelihood of receiving standard-of-care treatment may vary by patient race. 15 Therefore, disparities in oncologic outcomes are likely influenced by key sociodemographic variables.…”
mentioning
confidence: 99%
“…Studies have consistently demonstrated decreased survival for solid tumors as well as hematologic malignancies among patients of certain racial and socioeconomic backgrounds 11,12 . Mechanisms underlying these disparities include differences in access to care and follow‐up, screening utilization, and health behaviors 13,14 . For specific malignancies, studies have also illustrated that the likelihood of receiving standard‐of‐care treatment may vary by patient race 15 .…”
mentioning
confidence: 99%
“…Racial discrimination is known to begin with the pipeline to professional training 15 , continue in applications and selection to the NHS 11 , through to inequalities in experiences and opportunities when employed 12 . Understanding of what actually works to support workforce diversity, at all career levels, is currently limited to certain elds or clinical specialisms, for example, emergency medicine 16 and oncology 17 , and more could be done to build upon learning in further and higher education about widening access and equality monitoring 18 .…”
Section: Introductionmentioning
confidence: 99%